World Hip Trauma Evaluation (WHiTE): framework for embedded comprehensive cohort studies - Costa, M; Griffin, X; Achten, J; Metcalfe, D; Judge, A; Pinedo Villanueva, R; Parsons, N (BMJ Publishing Group, 2016)
Introduction: Osteoporotic hip fractures present a significant global challenge to patients, clinicians and healthcare systems. It is estimated that hip fracture accounts for 1.4% of total social and healthcare costs in the established market economies. Methods and analysis: The World Hip Trauma Evaluation (WHiTE) was set up to measure outcome in a comprehensive cohort of UK patients with hip fracture. All patients in the cohort are treated under a single comprehensive treatment pathway. A core outcome set, including health-related quality of life, is collected on all the patients. This protocol describes the current multi-centre project that will be used as a vehicle to deliver a series of embedded observational studies. Ethics and dissemination: Research Ethics Committee approval was granted (Rec reference 11/LO/0927, approved 18/8/2011) and each hospital Trust provided NHS approvals. The study is registered with National Institute of Health Research Portfolio (UKCRN ID 12351) and the ISRTCN registry (ISRCTN63982700).